Role of surface chemistry in conditioning of materials in particle accelerators. Issue 1 (1st January 2023) - Sattonnay, G; Bilgen, S; Mercier, B; Longuevergne, D; Della-Negra, S; Ribaud, I
Abstract: For the vacuum scientists and the accelerator community, finding solutions to mitigate pressure rises induced by electron, photon and ion desorption, and also beam instabilities induced by ion and electron clouds is a major issue. Along the time, changes in the surface chemistry of vacuum chambers are observed during beam operations, leading to modifications of: outgassing rates, stimulated desorption processes and secondary emission yields (SEY). To understand the role of the surface chemistry of air exposed materials in the electron conditioning process, typical air exposed materials used in particle accelerators : thin film coatings (NEG, i.e a Ti-Zr-V alloy, and carbon), copper (and its oxides Cu2 O and CuO) and niobium were conditioned by low energy electron irradiation for a better understanding of electron-cloud effect. First, SEY was measured to understand the changes of surface conditioning upon particle irradiation; then, surface chemistry evolution after electron irradiation was investigated by both XPS and TOF-SIMS analyses using the ANDROMEDE facility at IJCLab. Finally, the relationship between the surface chemistry and the conditioning phenomenon will be discussed.